1998
DOI: 10.1037/0021-9010.83.6.892
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of applicant reactions to employment testing and test outcome feedback.

Abstract: Following a justice framework, the present study examined actual candidates taking selection tests to gain full-time employment. The reactions of 144 applicants for an entrylevel accounting job were examined in a real employment testing context at 3 time periods: before testing, after testing but before feedback on whether they passed or failed the test, and after test performance feedback. With controls for pretest perceptions, several of the 5 procedural justice measures (information known about the test, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
337
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(359 citation statements)
references
References 47 publications
17
337
4
1
Order By: Relevance
“…Distributive justice or outcome fairness refers to the fairness of outcomes or outcome favorability. Outcome favorability (e.g., pass or fail) is a key determinant of fairness (e.g., Bauer et al, 1998;Ployhart & Ryan, 1998), but process fairness is also important to applicant reactions (e.g., Bauer et al, 1998;Macan et al, 1994) and may interact with outcome favorability (Brockner, 2002;Brockner & Wiesenfeld, 1996). That is, although distributive justice is the primary determinant of fairness perceptions, procedural justice often shows incremental prediction of fairness after controlling for distributive justice.…”
Section: Information and Organizational Justice Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Distributive justice or outcome fairness refers to the fairness of outcomes or outcome favorability. Outcome favorability (e.g., pass or fail) is a key determinant of fairness (e.g., Bauer et al, 1998;Ployhart & Ryan, 1998), but process fairness is also important to applicant reactions (e.g., Bauer et al, 1998;Macan et al, 1994) and may interact with outcome favorability (Brockner, 2002;Brockner & Wiesenfeld, 1996). That is, although distributive justice is the primary determinant of fairness perceptions, procedural justice often shows incremental prediction of fairness after controlling for distributive justice.…”
Section: Information and Organizational Justice Theorymentioning
confidence: 99%
“…Gilliland's (1993) model, which is based in organizational justice theory (e.g., Greenberg, 1990), has received the greatest research attention (e.g., Bauer, Maertz, Dolen, & Campion, 1998;Gilliland, 1994). The model suggests that applicant outcomes and the organization's adherence to fairness rules affect applicants' perceptions of the organization, the selection process, and themselves.…”
mentioning
confidence: 99%
“…First they suggest that when applicants receive information regarding outcome favorability, they will be more influenced by the outcome rather than the procedures used during the selection process. This effect was consistent with the findings of Bauer et al (1998), who found that the predictive power of procedural perceptions in explaining behavioral outcomes declined once the outcome was known by the applicant. This self-reported perceptions of the process and self-attitudes when measured at the same point in the process.…”
Section: Naturalistic Changessupporting
confidence: 81%
“…In other words, applicants who do not receive the job generally perceive the selection process as less fair than those who do receive the job. For example, Bauer et al (1998) found that outcome favorability predicted organizational attractiveness, intentions toward the organization and general perceptions of test fairness more consistently than procedural aspects of the selection system. Similarly, Self-Serving Bias 9 Ryan and Chan (1999) found that applicants who failed a licensure exam had more negative attitudes toward the test than those who failed it.…”
Section: Self-serving Biasmentioning
confidence: 99%
See 1 more Smart Citation